Innovation Led Renewable Energy Consumption in OECD Nations: Evidence from Fourier Functions - Qamruzzaman, Md; Swarna, Sharmin Rahman (International Journal of Energy Economics and Policy, 2025)
This study investigates how technological, environmental, and financial innovations influence renewable energy consumption in OECD countries, with implications for sustainable energy transitions. Using CS-ARDL and Fourier-based econometric techniques, this study analyzes panel data from 2004 to 2022 across OECD countries to capture both symmetric and asymmetric relationships and long-run dynamics. Technological innovation significantly promotes renewable energy consumption, with a 1% increase leading to a 0.1385% rise in the long run. Environmental innovation also fosters renewable adoption (0.1273%), driven by green policies and eco-technologies. Financial innovation exerts the strongest effect (0.1891%), highlighting the role of green finance, bonds, and inclusive financial mechanisms. However, global uncertainty negatively impacts renewable energy investment and usage (−0.1215%). Control variables like financial development show a positive effect, while natural resource rents inhibit renewable uptake. Strong long-run equilibrium adjustment ensures model stability. These results underscore the synergistic value of innovation and governance for advancing energy sustainability in OECD nations. This study is novel in integrating technological, environmental, and financial innovation dimensions using a Fourier-based CS-ARDL approach, accounting for cross-sectional dependence and nonlinearity. It uniquely captures asymmetric effects across OECD nations and links macro-level innovation drivers to renewable energy consumption in the context of uncertainty and institutional quality. Governments should enhance green finance mechanisms, incentivize R&D in clean technologies, and ensure institutional stability to stimulate innovation-led renewable energy transitions aligned with climate and sustainability commitments.